Dupilumab, corticosteroids and their combination for the treatment of bullous pemphigoid - Guirong Liang; Hua Qian; Chao Sun; Hanmei Zhang; Zhiliang Li; Suo Li; Ke Jing; Chenjing Zhao; Yuan Wang; Ruiyu Xiang; Xiaoguang Li; Suying Feng (Anais Brasileiros de Dermatologia)
Abstract Background: Conventional systemic corticosteroid therapy for bullous pemphigoid (BP) has been challenged due to severe adverse events. Dupilumab has emerged as an alternative therapeutical option of BP patients. Objectives: To evaluate the efficacy of dupilumab monotherapy and the combination with medium/low-dose corticosteroids for BP treatment. Methods: Thirteen, twenty-four and thirty-two BP patients treated with Dupilumab monotherapy (Dupi group), dupilumab combined with corticosteroids (Dupi + CS group), and corticosteroid monotherapy (CS group), respectively, were retrospectively analyzed for various clinical and laboratory parameters. Results: In the Dupi group, the total Bullous Pemphigoid Disease Area Index (BPDAI) Total, Erosion/Blister, Urticaria/Erythema and Itching NRS scores were all reduced significantly after 2-4 weeks of treatment, but the BPDAI Mucosal Score was not changed significantly at the end of the overextended time of treatment. All the above clinical parameters and many laboratory parameters (including the serum anti-BP180 autoantibodies [IgG] level, blood eosinophil count, and percentage) were significantly reduced in both Dupi + CS and CS groups after treatment, but no statistical differences were found in the reduction rates of these parameters between the two groups. However, the Dupi + CS group had less baseline dose and cumulative dosage of prednisone at the time of disease control, and fewer adverse effects were reported than the CS group. Study limitations: The retrospective design and small clinical sample size of the Dupi group. Conclusions: For BP patients, dupilumab monotherapy based on the treatment of atopic dermatitis can significantly improve skin lesions and pruritus symptoms but may be ineffective for oral mucosal lesions. The combination of dupilumab and medium/low-dose corticosteroids can achieve the same effect of corticosteroid therapy with superior safety.